2021
DOI: 10.1136/bmjophth-2020-000661
|View full text |Cite
|
Sign up to set email alerts
|

Retinal arteriolar calibre and venular fractal dimension predict progression of proliferative diabetic retinopathy 6 months after panretinal photocoagulation: a prospective, clinical interventional study

Abstract: ObjectiveWe examined the hypothesis that baseline retinal vascular geometry in patients with proliferative diabetic retinopathy (PDR) predicts disease activity 6 months after panretinal photocoagulation (PRP).Methods and analysisWe included 47 eyes from 40 patients with treatment-naïve PDR in a 6-month prospective study. Diagnosis of PDR and disease activity was evaluated by wide-field fluorescein angiography (Optomap, Optos, Dunfermline, Scotland, UK). At baseline and 6-month follow-up, the retinal vessel geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Talu et al [ 96 ] demonstrated that fractal dimension were higher in mild non-proliferative DR (NPDR), but lower in moderate and especially severe NPDR when compared to controls. Torp et al [ 98 ] demonstrated that retinal venular fractal dimension predicted disease activity 6 months after panretinal photocoagulation, suggesting it may serve as a biomarker of treatment efficacy. The challenges of utilising the fractal dimension in DR have been described by Forster et al [ 99 ].…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…Talu et al [ 96 ] demonstrated that fractal dimension were higher in mild non-proliferative DR (NPDR), but lower in moderate and especially severe NPDR when compared to controls. Torp et al [ 98 ] demonstrated that retinal venular fractal dimension predicted disease activity 6 months after panretinal photocoagulation, suggesting it may serve as a biomarker of treatment efficacy. The challenges of utilising the fractal dimension in DR have been described by Forster et al [ 99 ].…”
Section: Fractal Dimensionmentioning
confidence: 99%